Analisis Pendapatan Usahatani Cabai Rawit di Desa Raanan Baru Kecamatan Motoling Barat Kabupaten Minahasa Selatan - Kodongan, Friska; Rengkung, Leonardus Ricky; Waney, Nordy Fritsgerald Lucky (AGRI-SOSIOEKONOMI, 2024)
This research aims to analyze the income obtained from cayenne pepper farming activities in one planting season in Raanan Baru Village, West Motoling District, South Minahasa District. This research was conducted from July to September 2023. The data collection method used was primary and secondary data. Respondents in this study consisted of 10 people using purposive sampling. The data analysis used is quantitative descriptive analysis. The results of this research show that each farmer respondent has a different income. The average income earned by respondents from cayenne pepper farming in Raanan Baru Village, West Motoling Sub-District, South Minahasa District is IDR20,660,303 per planting season is obtained from the difference between the average revenue of IDR29,950,000 and the average total cost of IDR10,619,697.